2020
DOI: 10.3390/ejihpe10010036
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Perception of Risk and Preventive Behaviors toward Premarital Sexual Practice among In-School Adolescents

Abstract: Premarital Sexual Practice (PSP) among adolescents usually involves sexually risky behaviors, such as multiple sexual partners and inconsistent or non-condom use. These behaviors, in combination with other underlining factors, undermine the overall outcomes of Adolescent Sexual and Reproductive Health (ASRH). To assess the adolescents’ knowledge, attitudes and perception of risk and preventive behaviors towards PSP, a school-based analytical cross-sectional study was conducted among a sample of 423 students ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…To give an example of the studies on this subject, the effect of information on HIV/AIDS on the sexual practices of sex workers was not found significant in Brazil (Patricio et al, 2019). Similarly, multicomponent communitybased intervention study in Zimbabwe found lack of relationship between HIV knowledge and HIV risk of the participants (Yau et al, 2020). These findings could show that individuals do not act rationally and in a planned manner in their sexual relations.…”
Section: Introductionmentioning
confidence: 95%
“…To give an example of the studies on this subject, the effect of information on HIV/AIDS on the sexual practices of sex workers was not found significant in Brazil (Patricio et al, 2019). Similarly, multicomponent communitybased intervention study in Zimbabwe found lack of relationship between HIV knowledge and HIV risk of the participants (Yau et al, 2020). These findings could show that individuals do not act rationally and in a planned manner in their sexual relations.…”
Section: Introductionmentioning
confidence: 95%
“…The median age of female students was 21 years and we note that young people are sexually active during this period of their lives. 16,17 However, the proportion of female students who use condoms during sexual intercourse remains low. This can be explained by the unavailability of condoms or by the high cost of condoms (a box of 24 condoms costs 6480 CFA Francs equivalent to 9.87 Euros).…”
Section: Articlementioning
confidence: 99%
“…Several studies on students show that special attention should be paid to this target group. 16,17 Some of the results of these studies show that most young people have unprotected sex with their partners, others have several sexual partners, and some have sex under the influence of alcohol or drugs. 11,[18][19][20][21] In Togo, few data exist on vaccination against STIs, notably hepatitis B (HBV) and human papillomavirus (HPV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O jovem pode ficar 'refratário' e reclamar da supervisão dos pais. É necessário sensibilidade para modificar atitudes de excesso de vigilância, valorizando e incentivando autonomia dos jovens (Yau et al, 2020). Apesar de acontecer esta separação progressiva da família, Matos & Lembruber (2017) nos chamam a atenção para a necessidade deste adolescente se sentir incluído na vida familiar, respeitado dentro de um espaço em que sua espontaneidade e nuances possam ser expressas.…”
Section: B-chegada Da Adolescência: Influência No Acompanhamento Odon...unclassified